Model For Testing The İmpact Of Motivational Factors Of Nascent Entrepreneurs On Business Surviving Success - Christoph Ernst Wilken Kisker (European Scientific Journal, ESJ, 2016)
The development of founded companies is influenced by a wide variety of factors. In order to predict the chance of success for entrepreneurship, the relationship between these factors and the business surviving success has to be analyzed. Research indicates an influence of the motivation of entrepreneurs and financial success. The object of this paper are nascent entrepreneurs and the subject is the motivational structure of nascent entrepreneurs. Methods of the paper are literature review, factor analysis and calculated model. Aim of the paper is building a relationship between the motivation of entrepreneurs and the business surviving success of the founded companies. The result of the paper is the ‘four force of entrepreneurial motivation’ model, which helps to analyses the relationship between the motivation of the entrepreneur and the business surviving success. It shows that the motivation of entrepreneur can be clustered in ‘financial reward’, ‘need for achievement’, ‘social recognition’ and ‘independence. The business surviving success is calculated as the geometric mean of the return on sales over 3 years based on the expenses and revenue from the founded companies in the PSED II dataset. It is the first time that the motivation of entrepreneurs is set in relationship with the business surviving success. The study develops a new model to test the relationship between the motivation of entrepreneurs and the business surviving success. It is the first study, which uses the geometric mean of the return on sales over a time span of 3 years. The clustering of motivation from different studies is reviewed for the first time.